Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow